Finite element analysis of TMJ implant under clenching loads - Arabshahi, Zohreh (2012)
The temporomandibular joint is one of the most complex anatomical structures and is exposed to high stress conditions during daily movements. Replacing the joint is normally done only in severe cases as success rate of the replaced joint is not as encouraging as other joint replacements. The design of TMJ implant which includes material selection plays a significant role in its success. Two different biomaterials—Ti–6Al–4V and CoCrMo— under static loads simulating five clenching tasks were analysed in this study. A three dimensional model of an adult mandible was developed from Computed Tomography image dataset, as well as a generic TMJ implant with fixation. All the applied clenching tasks consisted of nine principle muscles. The results showed that both materials were totally safe under these loading conditions. However Ti–6Al–4V showed a comparatively lower stress level.